1997
DOI: 10.1111/1468-0092.00040
|View full text |Cite
|
Sign up to set email alerts
|

The Exploitation of Carnivores and Other Fur‐bearing Mammals during the North‐western European Late and Upper Paleolithic and Mesolithic

Abstract: The exploitation of large mammals, particularly large herbivores, has dominated perceptions of Upper Palaeolithic and Mesolithic subsistence behaviour in north‐western Europe. This paper critically reviews the evidence for the exploitation of a complementary resource which has received little attention within the archaeological literature — carnivores and other fur‐bearing mammals. Evidence for exploitation of individual species is described and discussed. A model is then developed to explain the apparent expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 20 publications
(22 reference statements)
0
26
0
2
Order By: Relevance
“…In this area, these changes are characterized by the presence of small game animals in the archaeological assemblages, whereas in other regions large mammals or medium game preys are more abundant (Charles 1997;Strauss 2006). Zooarchaeological studies reveal a clear economic change in relation to subsistence that shows its peak during the end of this chronological frame (Aura et al 2002;Villaverde et al 1996;Hockett and Haws 2003;Jones 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this area, these changes are characterized by the presence of small game animals in the archaeological assemblages, whereas in other regions large mammals or medium game preys are more abundant (Charles 1997;Strauss 2006). Zooarchaeological studies reveal a clear economic change in relation to subsistence that shows its peak during the end of this chronological frame (Aura et al 2002;Villaverde et al 1996;Hockett and Haws 2003;Jones 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Charles 1997). Evidence for frequent hafting at the site may relate to the construction of composite points or barbs similar to those recreated experimentally (Crombé et al 2001), whereas the impact blows identified by Yaroshevich (pers.…”
Section: Discussionmentioning
confidence: 96%
“…The main difference in relation to the classical predator-prey system is that, due to high adaptability and opportunistic behavior characterizing human survival strategies (Charles, 1997;Miotti & Salemme, 1999;Kusimba, 1999), the model does not include a parameter generating increased human mortality as prey becomes rare (because hunters can simply target another prey, e.g., a small-bodied one, or increase vegetal food ingestion). For simulations, I followed Alroy (2001) and evaluated the dynamics of 41 prey species (Table 1), hunted by a small initial population of 100 humans that had arrived in North America and started to grow at the relatively small rate of 2% a year (r = 0.02).…”
Section: Methodsmentioning
confidence: 99%